Relationship between vitamin D deficiency and gestational diabetes: a narrative review - Lin, Caiqiong; Liu, Haiwei (Frontiers in Endocrinology, 2024)
Vitamin D, often referred to as the “sunshine vitamin,” is an essential fat-soluble vitamin that plays a critical role in bone health and has been shown to improve insulin sensitivity and glucose tolerance. Vitamin D deficiency is prevalent among pregnant and pre-pregnancy women, which increases the risk of developing gestational diabetes mellitus (GDM), a common complication during pregnancy. Recent studies have explored various aspects of the relationship between vitamin D deficiency and GDM, including the mechanisms by which vitamin D affects glucose metabolism, the role of the vitamin D receptor gene, and the impact of routine vitamin D supplementation before and during pregnancy. This paper will review the current research progress in these areas.